The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/hjh.0b013e328349064c
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with nebivolol attenuates renal damage in Zucker diabetic fatty rats

Abstract: Our current finding underscores the importance of this therapy in hypertensive states concomitant with altered lipid and glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 54 publications
3
12
0
11
Order By: Relevance
“…The ability of nebivolol to increase renal reduced glutathione and to decrease renal malondialdehyde levels is consistent with the finding of Toblli et al . who reported that nebivolol increased the renal level of the antioxidant reduced glutathione and normalized renal malondialdehyde level in Zucker diabetic fatty rats. Recently, Akgullu et al .…”
Section: Discussionmentioning
confidence: 96%
“…The ability of nebivolol to increase renal reduced glutathione and to decrease renal malondialdehyde levels is consistent with the finding of Toblli et al . who reported that nebivolol increased the renal level of the antioxidant reduced glutathione and normalized renal malondialdehyde level in Zucker diabetic fatty rats. Recently, Akgullu et al .…”
Section: Discussionmentioning
confidence: 96%
“…Experimental data in animals with metabolic syndrome indicate that nebivolol has an actual protective role, not only in cardiovascular structures but also in renal tissue, in comparison with atenolol 58,63,80. Evaluation of immunoexpression of plasminogen activator inhibitor-1 and cell adhesion molecules, such as VCAM-1 and PECAM-1, in the vascular wall of diabetic rats which received nebivolol for 6 months showed favorable modification of these prothrombotic and vascular inflammatory markers when compared with atenolol 63.…”
Section: Comparative Impact On Cardiovascular Riskmentioning
confidence: 99%
“…Previous studies in humans and experimental animals have demonstrated an antioxidant effect of Nebivolol (Ignarro, 2004; Mollnau et al, 2003; Oelze et al, 2006; Whaley Connell et al, 2009, Varagic et al, 2010; Toblli et al, 2011; Moningka et al, 2012); therefore, we also examined the effect of Nebivolol on measures of systemic and renal oxidative stress and renal cortex antioxidant enzyme abundance. The 5/6 A/I model was associated with an increase in nitrotyrosine immunoreactivity and a decrease in mnSOD abundance in the renal cortex vs. control.…”
Section: Discussionmentioning
confidence: 99%
“…Nebivolol exerts short (4 weeks) and long (6 months) term renal protection in the 5/6 nephrectomy (Nx) model (Gschwend et al, 2009; Pires et al, 2007), the transgenic Ren 2 rat (Whaley-Connell et al, 2009; Hayden et al, 2010), high-salt fed spontaneously hypertensive rats (Varagic et al, 2010), and the zucker obese rat (Habibi et al, 2011; Toblli et al, 2011). In addition, we recently reported that nebivolol is protective against hypertension and CKD during chronic NOS inhibition with L-NAME, (Moningka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%